Enhancement in the double Higgs boson production by e+ e− annihilation and physics beyond the standard model. - Vásquez Tocora, Andrés Felipe [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
The main goal of this dissertation is to show the enhancement of the cross-section for the double Higgs production through pair annihilation by including effective interactions and through the non-perturbative Sommerfeld effect. Bounds to some Wilson coefficients were obtained from such enhancement, this in the scenarios of the future e+ e− -colliders (FCC-ee, ILC, CLIC). In order to achieve this, some computational tools were implemented: FeynRules, FeynArts, FormCalc, and LoopTools. It is also shown the enhancement of the double Higgs production in 2HDM and MSSM, discussing the general framework of these two models. In addition, it is studied the threshold behavior of the cross-section for the double Higgs production when a hidden sector couples to the Higgs boson, yielding resonances below the threshold energy due to non-perturbative effects. We study the Sommerfeld effect in the double Higgs production in the scenario of e+ e− -colliders. The enhancement is discussed as generated from a hidden sector coupled to the Higgs boson. Below and above threshold enhancements are presented. Such analysis is of importance in the ILC project, which will operate up to the threshold energy √s = 250 GeV. The results has been achieved by the use of computational tools like FeynArts, FormCalc, and LoopTools.

O objetivo principal dessa dissertação é, mostrar o aprimoramento da seção de choque para a produção em dobro dos bósons de Higgs, por meio de aniquilação de pares, incluindo interações efetivas e através do efeito não perturbativo de Sommerfeld. De tais aprimoramentos, os limites para alguns coeficientes de Wilson foram obtidos, isso nos cenários de futuros aceleradores de e+e- (FCC-ee, ILC, CLIC). Para atingir estes resultados, algumas ferramentas computacionais foram implementadas: FeynRules, FeynArts, FormCalc e LoopTools. Também, é mostrado o aprimoramento da produção em dobro de bósons de Higgs no “2HDM” e “MSSM”, discutindo o marco geral desses dois modelos. Além disso, foi estudado o comportamento, perto do limite de produção, da seção de choque da produção em dobro dos bósons de Higgs, quando um setor escondido é acoplado ao Higgs, produzindo ressonâncias abaixo da energia limite de produção, devido à efeitos não perturbativos.
Aprimoramento na produção em dobro de bóson de Higgs por aniquilação de e+ e− e física além do modelo padrão.
Keywords: Higgs boson production; Sommerfeld effect; Beyond the standard model; Effective field theory